Rotational Three-dimensional OCTA: a Notable New Imaging Tool to Characterize Type 3 Macular Neovascularization - Borrelli, Enrico (Sci Rep, 2019)
This study explored whether rotational three-dimensional (3D) visualization of optical coherence tomography angiography (OCTA) volume data may yield valuable information regarding type 3 macular neovascularization (MNV). In this retrospective, cross-sectional study, we collected data from 15 eyes (13 patients) with treatment-naïve type 3 MNV in their post-nascent stage and age-related macular degeneration (AMD). Subjects were imaged with the SS-OCT system (PLEX Elite 9000, Carl Zeiss Meditec Inc., Dublin, CA, USA). The OCTA volume data were processed with a prototype volume projection removal algorithm and then analyzed using volumetric visualization techniques in order to obtain a 3D visualization of the region occupied by type 3 MNV. The two-dimensional and three-dimensional OCTA images were investigated. Mean ± SD age was 75.1 ± 7.4 years. BCVA was 0.42 ± 0.21 LogMAR in the study eyes. Considering the cohort of analyzed eyes, on rotational 3D OCTA images, a total of 35 neovascular lesions (vs 22 lesions detected on 2D OCTA images) rising from the deep vascular complex and variably spanning the outer retinal layers and eventually reaching the RPE/sub-RPE space were detected. Nine of 35 lesions had a saccular shape, while the remaining cases had a filiform shape. On rotational 3D OCTA images, these lesions were inclined on the three planes, instead of perpendicular to the RPE/Bruch’s membrane. In conclusion, this study used an algorithm to obtain rotational three-dimensional visualization of type 3 MNV. This approach seems to increase the detection rate for these lesions and to be useful to offer new insight into type 3 MNV.